Mechanism of Xiezhuo Huayu Yiqi Tongluo Formula in the Treatment of Uric Acid Nephropathy Based on Network Pharmacology, Molecular Docking, and In Vivo Experiments. (21st February 2023) - Fan, Lifei; Guo, Yuqin; Wu, Qingmei; Hu, Tingting; Chen, Xiaomei; Guo, Jing; Liu, Ying; Lu, Yuhui; Lin, Min
Abstract : Background . Xiezhuo Huayu Yiqi Tongluo Formula (XHYTF) consists of 14 Chinese herbal medicines. In this study, we investigated the potential mechanism of XHYTF in the treatment of uric acid nephropathy (UAN) through network pharmacology, molecular docking, and in vivo methods. Methods . Using various pharmacological databases and analysis platforms, information on the active ingredients and targets of Chinese herbal medicine was collected, and UAN disease targets were retrieved using OMIM, Gene Cards, and NCBI. Then common target proteins were integrated. A Drug-Component-Target (D-C-T) map was constructed to screen core compounds and build a protein-protein interaction (PPI) network. Further, Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed for common targets, and a Drug-Component-Target-Pathway (D-C-T-P) network diagram was constructed. The molecular docking simulation was performed to verify the binding affinity between core components and hub targets. Subsequently, the UAN rat model was established, followed by the collection of serum and renal tissues. The expression levels of indicators in the serum were determined using an enzyme-linked immunosorbent assay. The pathological changes of renal tissues were detected using H & E staining and Masson staining. The expression of related proteins in renal tissue was detected by western blot. Results . In the study, 216 active ingredients and 439 targets in XHYTF were screened, and 868 targets were identified as being related to UAN. Among them, 115 were common targets. Based on the D-C-T network, quercetin, luteolin, β -sitosterol, and stigmasterol were observed to be the key active ingredients of XHYTF that were effective against UAN. The analysis of the PPI network revealed TNF, IL6, AKT1, PPARG, and IL1 β as the 5 key targets. GO enrichment analysis revealed that the pathways were mainly concentrated in cell killing, regulation of signaling receptor activity, and other activities. Subsequently, KEGG pathway analysis revealed that multiple signaling pathways, including the HIF-1, PI3K-Akt, IL-17, and other signaling pathways, were closely related to the action of XHYTF. All 5 key targets were confirmed to interact with all core active ingredients. In vivo experiments indicated that XHYTF significantly reduced blood uric acid and creatinine levels, alleviated inflammatory cell infiltration in kidney tissues, reduced the levels of serum inflammatory factors such as TNF- α and IL1 β, and ameliorated renal fibrosis in rats with UAN. Finally, western blot revealed decreased levels of PI3K and AKT1 proteins in the kidney, which confirmed the hypothesis. Conclusion . Collectively, our observations demonstrated that XHYTF significantly protects kidney function, including alleviation of inflammation and renal fibrosis via multiple pathways. This study provided novel insights into the treatment of UAN using traditional Chinese medicines.